Medicolegal Investigation of Burn Injury Patterns in Bintan, Indonesia: Implications for Scene Reconstruction and Criminal Prosecution - Aziz, Amalia (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Burn injuries pose a significant public health challenge in Indonesia, with Bintan being no exception. Medicolegal investigations of burn injuries are critical in determining the cause and manner of death, aiding scene reconstruction, and supporting criminal prosecution when necessary. Methods: This retrospective study analyzed 150 medicolegal autopsy reports of burn injury cases from Bintan between 2018 and 2023. Data collected included demographics, burn injury characteristics, cause of death, and circumstances surrounding the incident. Statistical analysis was performed to identify patterns and associations. Results: The majority of victims were male (65%), with a mean age of 38 years. Scalds were the most common type of burn (45%), followed by flame burns (35%). Most deaths resulted from complications of burn injuries, such as sepsis and respiratory failure. Scene investigation and witness testimonies were crucial in differentiating between accidental, suicidal, and homicidal burn injuries. Conclusion: Medicolegal investigations of burn injuries in Bintan play a vital role in scene reconstruction and criminal prosecution. Understanding the patterns and circumstances surrounding burn injuries can aid in developing preventive strategies and improving the justice system's response to such cases.